EVALUATION OF THE SACRIFICIAL ANODE CATHODIC PROTECTION OF CARBON STEEL IN 0.5M NACL USING EXPERIMENTAL DESIGN (Journal of Engineering, 2008)
This study examined the effect of Temperature (T); flow rate(F); and pH ; on the zinc consumption as sacrificial anode in cathodic protection of steel pipe carrying saline solution (i.e., 0.5 M NaCl) using a 23 factorial design. Rates of zinc consumption during cathodic protection were measured by weight loss technique and it ranges from 7.5x10-3 to 98.9x10-3 g/cm2.day. For the system under investigation, the cell responsible for cathodic protection is Zn/NaCl/Fe .It was found that both temperature and flow rate increases the zinc consumption while pH decreases it sharply.It was found also that the interaction between the temperature and pH is the dominant term compared with other interactions.